2021
DOI: 10.1016/j.ejmp.2021.03.008
|View full text |Cite
|
Sign up to set email alerts
|

The promise of artificial intelligence and deep learning in PET and SPECT imaging

Abstract: This review sets out to discuss the foremost applications of artificial intelligence (AI), particularly deep learning (DL) algorithms, in single-photon emission computed tomography (SPECT) and positron emission tomography (PET) imaging. To this end, the underlying limitations/challenges of these imaging modalities are briefly discussed followed by a description of AI-based solutions proposed to address these challenges. This review will focus on mainstream generic fields, including instrumentation, image acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 183 publications
(72 citation statements)
references
References 157 publications
(177 reference statements)
0
70
0
2
Order By: Relevance
“…A number of studies have demonstrated the potential of radiomic analysis in survival analysis and prediction of treatment outcome [12][13][14][15][16]. Oikonomou et al [17] investigated the predictive power of radiomic features along with maximum standardized uptake value extracted from PET/CT images of lung cancer patients treated with stereotactic body radiotherapy (SBRT).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated the potential of radiomic analysis in survival analysis and prediction of treatment outcome [12][13][14][15][16]. Oikonomou et al [17] investigated the predictive power of radiomic features along with maximum standardized uptake value extracted from PET/CT images of lung cancer patients treated with stereotactic body radiotherapy (SBRT).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in artificial intelligence, specifically deep learning (DL), have revolutionized the domain of computer vision and image processing. In the context of medical imaging, DL has been successfully deployed in challenging tasks, such as image segmentation/interpretation, cross-modality image translation, image denoising, radiotherapy treatment planning, and outcome prediction [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Debasis Mitra developed a Spline Initialized Factor Analysis of Dynamic Structures (SIFADS) algorithm ( 41 ), which performed well in animal and human experiments and significantly reduced image noise and improved image quality. In addition, deep learning technology is developing rapidly and shows excellent potential in image acquisition and processing, which may be widely used in the future ( 42 ).…”
Section: Research Progress Of Imaging Methods For Detection Of Microvascular Angina Pectorismentioning
confidence: 99%